2017
DOI: 10.11138/mltj/2017.7.2.230
|View full text |Cite
|
Sign up to set email alerts
|

How to evaluate bone tunnel widening after ACL reconstruction - a critical review

Abstract: SummaryBackground: Comparing different imaging modalities and methods for assessment tunnel widening after ACL reconstruction and providing a detailed evidence-based literature overview. Methods: PubMed was searched from 1970 to 2016 using the terms "ACL reconstruction" and "tunnel" and "imaging" or "CT" or "computerized tomography" or "MRI" or "magnetic resonance imaging" or "radiographs". 647 studies were found. 575 articles were excluded due to absence of specific radiological measurement methods of tunnel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“… 26 Three-dimensional CT has been employed to evaluate the size of the bone tunnel in anterior cruciate ligament (ACL) reconstruction. 9 , 27 CT was chosen over magnetic resonance imaging because of the higher bony spatial resolution and the ease of choosing the image plane to accurately evaluate the distance between the anchor and the FOT. This distance was compared between the cohorts.…”
Section: Methodsmentioning
confidence: 99%
“… 26 Three-dimensional CT has been employed to evaluate the size of the bone tunnel in anterior cruciate ligament (ACL) reconstruction. 9 , 27 CT was chosen over magnetic resonance imaging because of the higher bony spatial resolution and the ease of choosing the image plane to accurately evaluate the distance between the anchor and the FOT. This distance was compared between the cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…Third, for bone tunnel size measurement, computed tomography (CT) was not employed. Recently, it has been reported that CT scans may be the most suitable tool to evaluate bone tunnel size [47]. CT scans could be more sensitive for detecting the early bone tunnel findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several graft options have been described including allografts, patellar or quadricipital autologous tendons, but semitendinosus and gracilis flexor muscles are more frequently used. (2,8,12) Regardless of the type of graft used for reconstruction, all undergo a process known as ligamentization, in which the graft matures through revascularization and remodeling (2,13,20). However, little is known about how the graft evolves in terms of hypertrophy, hypotrophy, elongation or shortening in the immediate post-operative period.…”
Section: Introductionmentioning
confidence: 99%